Obesity-associated inflammation countered by a Mediterranean diet: the role of gut-derived metabolites - Florkowski, Melanie; Abiona, Esther; Frank, Karen M.; Brichacek, Allison L. (Frontiers in Nutrition, 2024)
The prevalence of obesity has increased dramatically worldwide and has become a critical public health priority. Obesity is associated with many co-morbid conditions, including hypertension, diabetes, and cardiovascular disease. Although the physiology of obesity is complex, a healthy diet and sufficient exercise are two elements known to be critical to combating this condition. Years of research on the Mediterranean diet, which is high in fresh fruits and vegetables, nuts, fish, and olive oil, have demonstrated a reduction in numerous non-communicable chronic diseases associated with this diet. There is strong evidence to support an anti-inflammatory effect of the diet, and inflammation is a key driver of obesity. Changes in diet alter the gut microbiota which are intricately intertwined with human physiology, as gut microbiota-derived metabolites play a key role in biological pathways throughout the body. This review will summarize recent published studies that examine the potential role of gut metabolites, including short-chain fatty acids, bile acids, trimethylamine-N-oxide, and lipopolysaccharide, in modulating inflammation after consumption of a Mediterranean-like diet. These metabolites modulate pathways of inflammation through the NOD-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome, toll-like receptor 4 signaling, and macrophage driven effects in adipocytes, among other mechanisms.